SUITABILITY OF SOIL TEST PROCEDURES FOR PREDICTING RESPONSE OF FLOODED RICE TO ZINC APPLICATION ON CALCAREOUS SOILS (Biological Sciences - PJSIR, 2022)
Zinc (Zn) deficiency is wide-spread in agricultural crops produced on alkaline calcareous soils of Pakistan. Agreenhouse study was, therefore, undertaken on six soil series of rice area for evaluating the suitability of differentextractants for extracting available zinc and to determine the critical soil Zn values for predicting rice response to Znapplication. Zinc treatments were nil and 10 mg Zn kg" soil. Rice variety KS 282 was the test variety. Results revealedthat DTPA extractable Zn in the soil had positive correlation with relative dry matter yield, tillers (in control pots), Znconcentration and its uptake in rice. Similarly, AB-DTPA extractable Zn was significantly correlated with the numberof tillers/plants dry matter yield and Zn uptake in rice. Mehlich-3 extractable Zn had highly significant correlation withrelative dry matter yield and Zn concentration in rice. Zinc extracted by HCI was significantly correlated with the numberof tillers/plant and dry matter yield and it has highly significant correlation with Zn uptake in rice. Ammonium acetateextractable Zn was neither correlated with rice growth parameters nor with Zn concentration and its uptake in rice.Critical values ofZn determined were: DTPA, 0.99 mg Zn kg': AB-DTPA, 1.22 mg Zn kg': Mehlich-3, 2.47 mg Zn(dm ')" and HCl, 0.34 mg Zn kg' soil. The AB-DTPA procedure of monitoring Zn availability in soils is preferred sinceit is a multielement soil test.